Pelatihan Penelitian Tindakan Kelas (PTK) Bagi Guru Biologi dan IPA Kota Salatiga: Strategi Peningkatan Kompetensi Penelitian Berbasis Kelas - Situmorang, Risya; Keliat, Natalia Rosa; Hastuti, Susanti Pudji; Atmojo, Wawan Pat; Halim, Vivian Yolanda; Priatama, Rafla Galang (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The Classroom Action Research (CAR) training for Science and Biology teachers in Salatiga aims to enhance pedagogical competence through a research-based approach. The implemented activities adopted a collaborative-participatory model, involving eight teachers through three main stages: (1) a joint needs identification with the local teachers' working group (MGMP), (2) intensive training across four interactive sessions, and (3) continuous mentoring. The training methods combined the presentation of conceptual material (CAR framework, data collection techniques), hands-on proposal drafting practice, and simulations on using research tools like Mendeley for reference management. Evaluation results indicated positive outcomes, with 100% of participants rating the facilitators as highly competent and 87.5% stating the material was presented clearly. However, a need for deepening practical aspects was identified, as 12.5% of participants still experienced difficulties in application. Thematic analysis of the feedback revealed three main recommendations: (a) increasing the portion of case-based learning activities using real examples, (b) developing applied biology-based modules, and (c) integrating technology such as digital microscopy in advanced training. The program's success is reflected in 80% of participants' ability to design relevant CAR proposals during the training, and the establishment of an online learning community for post-activity mentoring. These findings emphasize the importance of a teacher training model that combines applicable theory, intensive mentoring, and technological support, particularly to bridge the gap between academic research and classroom practice.